Dialysis headache: A literature review in the last 30 years - Souza, Mickael; Lima, Kerly Rocha; Fortes, Yasmine Maria Leódido; Silva-Neto, Raimundo; Filgueiras, Marcelo Carvalho (Headache Medicine, 2022)
Introduction According to the International Classification of Headache Disorders (ICHD-3), dialysis headache has no specific characteristics occurring during and caused by haemodialysis. It resolves spontaneously within 72 hours after the haemodialysis session has ended. Objective To describe the prevalence, clinical features, associated symptoms and risk factors of dialysis headache. Methods Based on a literature search in the major medical databases and using the descriptors“dialysis headache”, “hemodialysis and headache” and “renal dialysis and headache”we included articles published between 1992 and 2022. Of the 492articles found, only 9 met the inclusion criteria and were analyzed. Results We describe 444 patients (53.1% men and 46.9% women) diagnosed with dialysis headache, corresponding to 24.8% of those who underwent hemodialysis.The age ranged from 15 to 75 years. Pain occurred predominantly from the third hour of hemodialysis (65.8%), lasting less than four hours (71.7%), located bilaterally (63.1%), pulsatile (58.5%) and moderate intensity (68.9%).The most frequent associated symptoms were photophobia or phonophobia (71.5%), vertigo (22.3%) and nausea and/or vomiting (16.5%). Conclusion This review showed a high prevalence of dialysis headache in patients undergoing hemodialysis and that the clinical characteristics, treatment and prevention are still poorly studied.